2022
DOI: 10.3390/su141912190
|View full text |Cite
|
Sign up to set email alerts
|

Study on Design and Deformation Law of Pile-Anchor Support System in Deep Foundation Pit

Abstract: In this study, a deep foundation pit project of Nanlishi Road in the Xicheng District of Beijing was taken as the engineering background. Based on the monitoring method of that project and referring to its design scheme principle, this study applied advanced monitoring technology methods such as anchor axial force and deep horizontal displacement monitoring. The mechanism of pile–soil interaction, the stress change and deformation law of the three-pile and two-anchor support systems of deep foundation pits, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…However, due to the differing geological conditions in various regions and the lag in corresponding theoretical system updates, frequent accidents during excavations have occurred [ 3 , 4 , 5 ]. Through a comprehensive analysis of various excavation accidents, two main types were identified: one is the collapse of the excavation itself, caused by the instability of the excavation support structure [ 6 , 7 , 8 ], and the other is the overturning of the excavation due to excessive settlement around the excavation [ 9 , 10 , 11 ]. A further analysis of the destruction mechanisms based on the accident type revealed that approximately 90% of excavation safety issues are attributed to the mutual influence of excavation seepage and soil consolidation [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the differing geological conditions in various regions and the lag in corresponding theoretical system updates, frequent accidents during excavations have occurred [ 3 , 4 , 5 ]. Through a comprehensive analysis of various excavation accidents, two main types were identified: one is the collapse of the excavation itself, caused by the instability of the excavation support structure [ 6 , 7 , 8 ], and the other is the overturning of the excavation due to excessive settlement around the excavation [ 9 , 10 , 11 ]. A further analysis of the destruction mechanisms based on the accident type revealed that approximately 90% of excavation safety issues are attributed to the mutual influence of excavation seepage and soil consolidation [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The development of urbanization is bringing more and more tests of traffic in cities. In order to ease traffic pressure, governments have taken various measurements, such as widening roads, building more flyovers, and developing underground traffic systems [1][2][3]. Among these measurements, underground traffic systems are the most effective since land resources are very scarce in cities.…”
Section: Introductionmentioning
confidence: 99%
“…The selection of support structures has a significant impact on foundation pits. Sun et al [17] studied the stress changes and deformation patterns of the three-pile and two-anchor support systems for deep foundation pits, as well as the stability of deep foundation pit supports. The results demonstrated that the lateral pressure of the formation gradually increased with the increasing excavation depth of the foundation, and the pre-stress of the anchor rod gradually increased until the excavation ended and tended to stabilize.…”
Section: Introductionmentioning
confidence: 99%